Effect of the Children’s Health Activity Motor Program on Motor Skills and Self-Regulation in Head Start Preschoolers: An Efficacy Trial - Robinson, Leah E.; Palmer, Kara K.; Bub, Kristen L. (Frontiers in Public Health, 2016)
Self-regulatory skills are broadly defined as the ability to manage emotions, focus attention, and inhibit some behaviors while activating others in accordance with social expectations and are an established indicator of academic success. Growing evidence links motor skills and physical activity to self-regulation. This study examined the efficacy of a motor skills intervention (i.e., the Children’s Health Activity Motor Program, CHAMP) that is theoretically grounded in Achievement Goal Theory on motor skill performance and self-regulation in Head Start preschoolers. A sample of 113 Head Start preschoolers (Mage = 51.91 + 6.5 months; 49.5% males) were randomly assigned to a treatment (n = 68) or control (n = 45) program. CHAMP participants engaged in 15, 40-minute sessions of a mastery climate intervention that focused on the development of motor skills over 5 weeks while control participants engaged in their normal outdoor recess period. The Delay of Gratification Snack Task was used to measure self-regulation and the Test of Gross Motor Development - 2nd Edition was used to assess motor skills. All measures were assessed prior to and following the intervention. Linear mixed models were fit for both self-regulation and motor skills. Results revealed a significant time*treatment interaction (p < .001). In regards to motor skills, post hoc comparisons found that all children improved their motor skills (p < .05), but the CHAMP group improved significantly more than the control group (p < .001). Children in CHAMP maintained their self-regulation scores across time while children in the control group scored significantly lower than the CHAMP group at the posttest (p < .05). CHAMP is a mastery climate movement program that may be an approach to enhance skills associated with healthy development in children (i.e., motor skills and self-regulation). This efficacy trial provided evidence that CHAMP helped maintain delay of gratification in preschool age children and significantly improved motor skills while participating in outdoor recess was not effective. CHAMP could help contribute to children’s learning related skills and physical development and subsequently to their academic success.